Confusing procedures with process when appraising the impact of cognitive bias modification on emotional vulnerability - Grafton, B; MacLeod, C; Rudaizky, D; Holmes, E; Salemink, E; Fox, E; Notebaert, L (Cambridge University Press, 2018)
If meta-analysis is to provide valuable answers, then it is critical to ensure clarity about the questions being asked. Here, we distinguish two important questions concerning cognitive bias modification research that are not differentiated in the meta-analysis recently published by Cristea et al (2015) in this journal: (1) do the varying procedures that investigators have employed with the intention of modifying cognitive bias, on average, significantly impact emotional vulnerability?; and (2) does the process of successfully modifying cognitive bias, on average, significantly impact emotional vulnerability? We reanalyse the data from Cristea et al to address this latter question. Our new analyses demonstrate that successfully modifying cognitive bias does significantly alter emotional vulnerability. We revisit Cristea et al's conclusions in light of these findings.